RECOGNITION OF EARTHQUAKE-PRONE AREA (M \(≥ 5.0\) ) APPLIED FOR NORTH VIETNAM AND ADJACENCY - Tuyen, Nguyen Huu; GORSHKOV, A.I.; Lu, Ngo Thi (Vietnam Journal of Earth Sciences, 2012)
Seismogenic nodes capable of earthquakes with M\(≥ 5.0\) have been identified in the Northern Vietnam that exhibit the highest seismic activity over the Vietnam territory. Recognition objects - morphostructural nodes - have been delineated with the morphostructural zoning (MZ) method and their classification into seismogenic nodes and non-seismogenic ones was performed with the pattern-recognition. With MZ we have compiled a morphostructural map (scale 1:1,000,000) for the study region. The map shows the hierarchical block-structure of the region, the network of boundary zones bounding blocks, and the loci of the nodes. A three-level hierarchy has been established for the blocks and their boundaries. The recorded M\(≥ 5.0\) earthquakes nucleate at the nodes delineated by MZ, i.e. ignoring the seismic record. Among all delineated nodes we recognized the seismogenic ones (D), prone to M\(≥ 5.0\) earthquakes, with the pattern recognition algorithm CORA-3. The performed recognition pinpoints a number of \(D\) nodes where events with M\(≥ 5.0\) have not been recorded to date.